Teknik Pengelolaan Stress Model Inkubasi Kelompok Budidaya Ikan Program Antisipasi Pandemi Berkelanjutan - Alqap, Sofwan (Universitas Tanjungpura, 2021)
The Covid-19 pandemic forced everyone laid off. When the situation recover, do not know. Will he/she return to similar work, do not sure. Continuing stress threats to many people. They need helps, to manage the emotional related impact, to build what new about sense, who he/she might be, to carry on a recent part. Psychological advices was given to develop a sustaining model for managing stress, enjoying, making hope, maintaining social contact, sharing each other, and being an incubator in effect to emerge a prosperous activity next. Social media have been a means to keep them in contact indicating the way was running well as the stress management model for low level of open workers who have lost their jobs, and generating new hope and interest from their online communication.